Development of pullulan‐based nanocomposite films reinforced with starch nanocrystals for the preservation of fresh beef. (1st November 2022) - Dai, Miaoqi; Xiong, Xiong; Cheng, Anwei; Zhao, Zhengtao; Xiao, Qian
Abstract: BACKGROUND: Incorporation of polysaccharide‐based nanofillers is an effective strategy to fabricate bio‐nanocomposite films with preferable mechanical, barrier, and surface hydrophobicity properties compared to pure biopolymer films. The objective of this research is to investigate the influence of starch nanocrystals obtained from native (NSNC) and waxy rice starch (WSNC) on the physical–chemical properties of pullulan‐based nanocomposite films and their preservation performance on fresh beef. RESULTS: Continuous SNCs network structure was observed for pullulan‐10% SNCs nanocomposite films, whereas the percolation network of SNCs was destroyed and became no longer continuous with increasing SNCs concentration up to 20% in pullulan films. Among the tested films, pullulan‐10% SNCs films showed the highest TS values, lowest WVP and OTR values, due to the formation of percolating SNCs network in pullulan matrix. It is noteworthy that the WVP and OTR values of pullulan‐10% WSNC films were significantly lower than that of pullulan‐10% NSNC films, probably due to higher hydrophobicity and crystallinity of WSNC compared with NSNC. Beef pieces coated with pullulan‐SNCs films had higher L * and a * values, lower TVB‐N, TBARS, and TVC values during 7 days' storage at 4 °C compared with samples coated with pullulan films. CONCLUSION: Pullulan‐SNCs nanocomposite films, especially pullulan‐WSNC films, could be potentially used as a coating material for fresh beef due to their desirable oxygen and water barrier properties. © 2022 Society of Chemical Industry.